Efeitos da ventilação não invasiva nas respostas fisiológicas e sensoriais ao exercício em pacientes com insuficiência cardíaca associada à Doença Pulmonar Obstrutiva Crônica - Souza, Aline Soares De [UNIFESP] (2019)
Aims: To analyze the effects of NIV on the physiological, sensorial and effort tolerance responses in patients with HF and HF associated with COPD. Methods: Incremental cardiopulmonary testing was performed in 19 patients (9 with coexisting COPD but with similar low left ventricular ejection fraction) were submitted to a constant loading protocol with different intensities (20%, 40%, 60% and 80% Wpeak) with serial measures of inspiratory capacity (CI). The last W/peak intensity was maintained up to the limit of effort tolerance (Tlim). Patients received Sham or NIV (bi-level) ventilation that was adjusted according to individual comfort. Results: Tlim increased with NIV in relation to Sham ventilation only in HF+COPD (P <0.05). NIV provided higher tidal volume and lower respiratory rate, shorter duty cycle with longer expiratory time, and higher mean inspiratory flow in both groups (P <0.05), despite the absence of changes in minute ventilation. It is important to emphasize that NIV improved IC (by ~ 0.5 l) across all exercise intensities only in HF+COPD. Assuming constant total lung capacity, NIV reduced operant lung volumes, thus decreasing inspiratory constraints. These beneficial consequences of NIV were associated with lower dyspnea Borg scores at the 80% peak and at the end of the exercise (p <0.05). Conclusion: NIV resulted in lower operative lung volumes and lower dyspnea. Tlim was higher even under high ventilatory stress, therefore, there was a better "quality" in the ventilatory responses during exercise only in the IC+COPD patients.